Global research trends on nutritional status and dialysis from a bibliometric perspective - Muna Shakhshir; Divya Vanoh; Sa’ed H. Zyoud (Discover Health Systems)
Abstract Background A significant lack of systematic data exists regarding the relationship between nutrition and dialysis, despite the recognized impact of poor nutrition on extended hospital stays and high mortality rates, especially in developing countries. To address this gap and stimulate further research, a comprehensive bibliometric analysis is crucial. This study aims to map the connections between dialysis and nutrition by examining citations, regional distributions, and research trends, ultimately identifying key areas of focus and providing an overview of current research in this field. Methods A comprehensive literature review on the relationship between nutritional status and dialysis therapy was conducted, and the Scopus database was used to identify relevant publications from 1952 to 2022. The selected articles met the preestablished inclusion criteria. VOSviewer software (version 1.6.20) was employed to analyse publication trends and key research areas within this body of literature. Results The study encompassed a total of 2,545 publications, reflecting a steady increase in published materials. Among these records, the United States emerged as the top contributor with 22.99%, followed by Japan at 6.95% and Italy at 6.29%. The primary funding source was NIDDK, accounting for 3.73%, with NIH ranking second at 2.48%. Before 2012, investigations in this field centred mainly on how nutritional parameters and anthropometric measurements affect dialysis outcomes; in the past decade, attention has broadened to encompass inflammation-related mortality in dialysis care and, more recently, dietary intake patterns, adherence, and patient behaviour. Conclusions This study presents a pioneering bibliometric analysis aimed at tracing the evolution of knowledge and trends in nutrition and dialysis therapy over the past seven decades. The findings offer a comprehensive overview, delineating the forefront of research on nutrition and end-stage renal disease, and providing valuable insights for scholars in this field. The study highlights a growing research emphasis on integrating inflammatory biomarkers, dynamic body composition monitoring, and multidisciplinary dietary interventions to enhance outcomes for dialysis patients.